Cognição Numérica de crianças pré-escolares brasileiras pela ZAREKI-K - Molina, Juliana; Ribeiro, Fabiana Silva; Santos, Flávia Heloísa Dos [UNESP]; Aster, Michael von (My University, 2015)
The Numerical Cognition is infl uenced by biological, cognitive, educational and cultural factors. It consists of a primary system, called Number Sense that would be innate and universal, also of secondary systems: the Calculation, implied to perform mathematical operations by means of symbols or words and Number Processing, which is divided into two components, Number Comprehension, related with the understanding of numerical symbols and Number Production, which includes reading, writing and coun-ting numbers. However, studies that show the development of these functions in children of preschool age are scarce. Therefore, aims of this study were to investigate numerical cognition in preschool Brazilian children to demonstrate the construct validity of the ZAREKI-K (A Neuropsychological Battery for the Assessment of Treatment of Numbers and Calculation for preschool children). The participants were 42 children of both genders, who attended public elementary schools; the children were evaluated by this battery and WISC-III. The results indicated signifi cant differences associated with age which children of 6 years had better scores on subtests related to Number Production, Calculation and Number Comprehension, as well moderate and high correlations between some subtests of both instruments, demonstrating the construct validity of the battery. In conclusion, preliminary normative data were obtained for ZAREKI-K. The analyses suggested that it is a promising tool for the assessment of numerical cognition in preschool children.Keywords: Mathematics, number, preschoolers, working memory, Developmental Dyscalculia.

Cognición Numérica de Niños Preescolares Brasileños por la ZAREKI-KResumenLa cognición numérica es infl uenciada por factores biológicos, educativos, cognitivos y culturales. Posee un sistema primario innato y universal, que es el Sentido Numérico y sistemas secundarios: el Cálculo, para realizar operaciones matemáticas por medio de símbolos o palabras y el Procesamiento Numérico, que se divide en dos componentes, la Comprensión Numérica, que implica la comprensión de los símbolos numéricos, y la Producción Numérica que incluye la lectura, escritura y conteo de números. Sin embargo, hay pocos estudios que muestran el desarrollo de estos sistemas en los niños de edad preescolar. Los objetivos de este estudio fueran investigar la cognición numérica en niños brasileños en edad preescolar y demostrar la validez de constructo de la ZAREKI-K (Batería Neuropsicológica para la Evaluación del Tratamiento de los Números y el Cálculo para los Niños en edad Preescolar; Weinhold-Zulauf, Schweiter, & von Aster, 2003). Los participantes fueron 42 niños de entre 5 y 6 años de edad, de ambos sexos, que estudiaban en escuelas públicas de educación preescolar, los niños fueron evaluados por la referida batería y la WISC-III. Los resultados indicaron que los niños de seis años presentaron mejores puntuaciones en las pruebas relacionadas con Producción Numérica, Cálculo y la Comprensión Numérica, así como las correlaciones altas y moderadas entre algunos subtest de ambos instrumentos, lo que demuestra la validez construirla batería. En conclusión, se obtuvieron datos preliminares normativos para el ZAREKI-K. Los análisis sugieren que este es un instrumento prometedor para la evaluación de la cognición numérica en niños preescolares.Palabras clave: Matemática, número, preescolar, memória operativa, Discalculia do Desenvol- vimento

A Cognição Numérica é infl uenciada por fatores biológicos, cognitivos, educacionais e culturais. Cons-titui-se tanto de um sistema primário, chamado de Senso Numérico que seria inato e de abrangência universal, quanto de sistemas secundários, como o Cálculo que está implicado a realização de operações matemáticas por meio de símbolos ou palavras e o Processamento Numérico, que se divide em dois componentes, a Compreensão Numérica, que está relacionada ao entendimento de símbolos numéricos e a Produção Numérica: que inclui a leitura, escrita e contagem de números. Entretanto, os estudos que evidenciam o desenvolvimento destas funções em crianças de idade pré-escolar são escassos. Diante disso os objetivos do presente estudo foram investigar a cognição numérica em crianças brasileiras pré--escolares e demonstrar a validade de construto da ZAREKI-K (Bateria Neuropsicológica para Avalia-ção do Tratamento dos Números e do Cálculo para Crianças pré-escolares). Participaram da pesquisa 42 crianças, entre 5 e 6 anos de idade, de ambos os sexos, estudantes de escolas públicas de educação pré-escolar, que foram avaliadas pelos subtestes da ZAREKI-K e WISC-III. Os Resultados indicaram diferenças signifi cativas associadas à idade em que crianças de 6 anos obtiveram melhores pontuações em subtestes relacionados a Produção numérica, Compreensão numérica e Cálculo, bem como correla-ções moderadas a fortes entre alguns subtestes de ambos os instrumentos, demonstrando a validade de constructo da bateria. Em conclusão, foram obtidos dados normativos preliminares para a ZAREKI-K, ademais as análises sugerem tratar-se de um instrumento promissor para a avaliação da cognição numé-rica em crianças pré-escolares.Palavras-chave: Matemática, número, pré-escolares, memória operacional, Discalculia do Desenvol- vimento.
Numerical Cognition in Brazilian preschool children by the ZAREKI-K
Keywords: Mathematics; Number; Preschoolers; Working memory; Developmental dyscalculia; Matemática; Número; Pré-escolares; Memória operacional; Discalculia do desenvolvimento